LOGISTICS TO STRENGTHEN THE COMPETITIVE POSITION OF COMMERCIAL ENTERPRISES - LUPAK, R.; RUDKOVSKY, O.; BEREZIVSKYI, Y. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the theoretical and methodological foundations of building a system of logistics, which involves strengthening the competitive position of commercial enterprises, taking into account the peculiarities of their activities in the market environment and the formation of full-fledged domestic resource competitive capital. The purpose of the article is a scientific substantiation of the conceptual provisions of logistics to strengthen the competitive position of commercial enterprises, taking into account different areas of formation and implementation of the overall competitive resource potential. The necessity of material and technical support at the decision of the trading enterprises of tasks concerning strengthening of competitive positions is substantiated. The need for a functional distribution of areas to strengthen the competitive position of commercial enterprises with a clear definition of the role of material and technical assets and on their basis the relationship of the whole set of elements of the competitive potential of the enterprise. The managerial aspects of material and technical support for strengthening the competitive position of trade enterprises are determined, taking into account the peculiarities of the development of their activities. The system interrelations of logistical support with marketing, logistical, information-communication, investment-innovative, intellectual-organizational, financial-resource direction of activity of trade enterprises are characterized, which together allows to achieve a sufficient level of strengthening of competitive positions. The scientific novelty of the study is to prove that logistics as an element of strengthening the competitive position of commercial enterprises involves dependence on a number of functional activities, which together form the resource base for solving strategic problems in a competitive environment.